2005
DOI: 10.1016/j.physleta.2004.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Resonances and adiabatic invariance in classical and quantum scattering theory

Abstract: We discover that the energy-integral of time-delay is an adiabatic invariant in quantum scattering theory and corresponds classically to the phase space volume. The integral thus found provides a quantization condition for resonances, explaining a series of results recently found in non-relativistic and relativistic regimes. Further, a connection between statistical quantities like quantal resonance-width and classical friction has been established with a classically deterministic quantity, the stability expon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The outer resonances constitute extremely broad background in the density of states because of their quite high leakage and they should be take into account in the study of the trace formula in open cavity [22,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outer resonances constitute extremely broad background in the density of states because of their quite high leakage and they should be take into account in the study of the trace formula in open cavity [22,33].…”
Section: Discussionmentioning
confidence: 99%
“…In Using BEM, we showed that the outer resonances universally exist as one group of QNMs in two-dimensional dielectric cavities irrespective of the geometry of cavity and, especially, exist as the nearly degenerate states in the slightly deformed cavity. The outer resonances constitute extremely broad background in the density of states because of their quite high leakage and they should be take into account in the study of the trace formula in open cavity [22,33].…”
Section: Discussionmentioning
confidence: 99%
“…on the right of the potential range, ±e i(−Knx−Ent/h) on the left of the potential range, (22) where the sign of the second line on the right-hand side depends on whether the solution is odd or even, we obtain…”
Section: Particle Number Conservationmentioning
confidence: 97%
“…In the comprehensive review [16] a number of definitions of the tunneling time have been given, among them the so-called phase time or group delay time and dwell time. The energy integral of timedelay, as shown in [17], is an adiabatic invariant in quantum scattering theory, and corresponds classically to an open image in phase space. It has long been considered that the two contributions of asymptotic phase times, the time spent in the barrier region and the self-interference delay during the approach to the barrier, may not be disentangled.…”
Section: Introductionmentioning
confidence: 99%